ROS robotics by example : learning to control wheeled, limbed, and flying robots using ROS Kinetic Kame /: learning to control wheeled, limbed, and flying robots using ROS Kinetic Kame. (2017) - Fairchild, Carol; Harman, Thomas L, 1942-
No abstract available